Strategi Penerapan Nilai-Nilai Qur’ani dalam Pendidikan Akhlaq dan Adab Santri - Subando, Joko; Pamungkas, Maulana Al Bana; Azhari, Pebri (Lembaga Yasin AlSys, 2024)
Education is the educator's conscious guidance towards the physical and spiritual development of the educated towards the formation of the primary personality. The formation of a noble personality is proof of success in Islamic education. This research is aimed at digging out the various strategies that can be done in the education of akhlaq and adab for pupils as well as any factors that affect the development of akhlak and the behavior of pupils. This research uses the library research method, which means the collection of data and information is carried out through the study of literature from various written sources. The results of the research show that many strategies can be done in the process of education akhlaq and adab either the strategy is done directly or indirectly. As well as found some influential factors so that there needs to be attention to such factors in the educational process of akhlak and adab.